2006
DOI: 10.1258/000456306776865179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alkaline phosphatase inhibitors on intracellular lipid accumulation in preadipocytes isolated from human mammary tissue

Abstract: Addresses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
7
32
0
Order By: Relevance
“…9,10 The present study has confirmed the parallel relationship between elevated ALP enzyme activity and cellular fat accumulation in abdominal subcutaneous adipose tissue. The intracellular deposition of lipid is the defining feature of the maturation of preadipocytes into adipocytes, a process termed "adipogenesis".…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…9,10 The present study has confirmed the parallel relationship between elevated ALP enzyme activity and cellular fat accumulation in abdominal subcutaneous adipose tissue. The intracellular deposition of lipid is the defining feature of the maturation of preadipocytes into adipocytes, a process termed "adipogenesis".…”
Section: Discussionsupporting
confidence: 84%
“…22 It should be noted that levamisole inhibits ALP activity in cell extracts of human preadipocytes. 10 This confirms that it is the tissue-non-specific form. Thus, levamisole only activates ALP activity in human preadipocytes with intact membranes, 10 suggesting that this process is modulated by factors residing in the cell membrane system, the identities of which are currently unknown.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations